Professional Asp.net MVC 5 - Galloway, Jon; Wildon, Brad; Allen, K. Scott; Matson, David (Indiana John Wiley & Sons, 2014)
Contents: A quick introduction to Asp.net MVC, Asp.net MVC 5 overview, installing MVC 5 and creating applications, the MVC application structure; The controller's Role, controller basics,...
Includes bibliography and index
Keywords: Công nghệ thông tin